A Well-Controlled PSG Layer on Silicon Solar Cells against Potential Induced Degradation. (29th January 2015) - Du, Chen-Hsun; Chen, Chien-Hsun; Lung, Chien-Hua; Chen, Sung-Yu; Li, Li-Yu; Lin, Yu-Hsuan; Yeh, J. Andrew
Abstract : This study proposes a promising silicon (Si) solar cell structure for reducing the potential induced degradation (PID) of crystalline Si solar cells. Phosphorous silicate glass (PSG) layers were carefully designed on an emitter layer, and the thickness of these layers (dPSG ) was controlled by adjusting the diffusion temperature and time. The results show that the power loss remarkably decreased from 31% (dPSG = 0 nm) to 11% (dPSG = 22.3 nm) and further decreased to less than 5% after a 48-h PID test when dPSG was higher than 23.3 nm. No additional process or equipment was required for producing this effective and low-cost solar cell.